2012
DOI: 10.1161/hypertensionaha.111.177485
|View full text |Cite
|
Sign up to set email alerts
|

Angiotensin-(1-9) Attenuates Cardiac Fibrosis in the Stroke-Prone Spontaneously Hypertensive Rat via the Angiotensin Type 2 Receptor

Abstract: Abstract-The renin-angiotensin system regulates cardiovascular physiology via angiotensin II engaging the angiotensin type 1 or type 2 receptors. Classic actions are type 1 receptor mediated, whereas the type 2 receptor may counteract type 1 receptor activity. Angiotensin-converting enzyme 2 metabolizes angiotensin II to angiotensin-(1-7) and angiotensin I to angiotensin-(1-9). Angiotensin-(1-7) antagonizes angiotensin II actions via the receptor Mas. Angiotensin-(1-9) was shown recently to block cardiomyocyte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
80
2
10

Year Published

2013
2013
2023
2023

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 91 publications
(104 citation statements)
references
References 44 publications
(44 reference statements)
5
80
2
10
Order By: Relevance
“…Por lo tanto, el eje del SRA a través de la ECA2 y de Ang-(1-9) podría ser un importante blanco terapéutico de la HTA. Recientemente, Flores-Muñoz et al, mostró en su modelo experimental de ratas "strole-prone" espontáneamente hipertensas (SPSHR) que Ang-(1-9) administrada en dosis de 100 ng·Kg-1·min-1 no modificó la PAS 22 . Estos resultados difieren del efecto antihipertensivo observado para Ang-(1-9) probablemente, debido a la menor dosis de Ang-(1-9) usada en ratas SPSHR comparada con nuestros estudios de regresión de la HTA 23 .…”
Section: Discussionunclassified
See 3 more Smart Citations
“…Por lo tanto, el eje del SRA a través de la ECA2 y de Ang-(1-9) podría ser un importante blanco terapéutico de la HTA. Recientemente, Flores-Muñoz et al, mostró en su modelo experimental de ratas "strole-prone" espontáneamente hipertensas (SPSHR) que Ang-(1-9) administrada en dosis de 100 ng·Kg-1·min-1 no modificó la PAS 22 . Estos resultados difieren del efecto antihipertensivo observado para Ang-(1-9) probablemente, debido a la menor dosis de Ang-(1-9) usada en ratas SPSHR comparada con nuestros estudios de regresión de la HTA 23 .…”
Section: Discussionunclassified
“…Ambos efectos estuvieron directamente relacionados a la administración de Ang-(1-9) y no mediados por Ang-(1-7). Éstos resultados son consistentes con estudios publicados que muestran que la admistración de Ang-(1-9) a ratas SPSHR disminuyó la fibrosis cardíaca 22 . El efecto antifibrótico fue bloqueado por el antagonista del AT2R.…”
Section: Discussionunclassified
See 2 more Smart Citations
“…Angiotensin 1-9 exerts beneficial effects on the heart, which consist in reduction of blood pressure, improvement of endothelial function and limitation of hypertrophy and fibrosis [38]. It has been suggested that these beneficial effects of Ang 1-9 can be achieved via angiotensin II type 2 receptor (AT2R), independently of its conversion to Ang 1-7 [38,39]. In addition to the favorable activity on cardiac dysfunction, ACE2 was reported to play a role in the hydrolysis of a large number of peptides, including apelin-13 and apelin-36, which are thus degraded to ineffective forms [40].…”
Section: Apelin/apj System Vs Renin-angiotensin System (Ras)mentioning
confidence: 99%